Abordaje del paciente pediátrico con neutropenia febril y enfermedad oncológica (2015)
Introduction: Febrile neutropenia in pediatric patients with oncological disease, is a common condition leading to high morbidity and mortality. The main cause is infection, meriting a timely and comprehensive study to identify its source and begin an early and a targeted therapy, it is necessary to know about this disease and its management. Objective: Perform a current review of this pathology by addressing its epidemiology, etiology, clinical diagnosis and treatment. Methods: Search in database like Cochrane Library, Medscape, Pubmed, RIMA, Ebscohost, HINARI, Dynamed, NEJM, using keywords like neutropenia, fever, infection, risk, neoplasia and treatment. We selected clinical practice guidelines, systematic reviews and randomized clinical trials. Discussion: It is a common situation mainly in patients with hematological malignancy and the cause of the fever is due to an infection whose etiologic agent varies according to origin of the case, use of intravenous catheters or prolonged and deep neutropenia. The diagnostic approach must be through physical examination and the use of diagnostic tools such blood count, acute phase reactants and polyculture. The use of prognostic models for risk stratification allows to guide the antibiotic treatment. Conclusion: Improving the knowledge of this disease, the diagnosis and treatment strategies, it has been able to improve survival and prognosis of this disease. MÉD UIS. 2015;28(3):353-62.